ANALISIS DISTRIBUSI DAN MARGIN PEMASARAN USAHATANI KACANG TANAH DI KECAMATAN PULUBALA KABUPATEN GORONTALO - Yusniawati Kai; Mahludin Baruwadi; Wawan K. Tolinggi (Agrinesia: Jurnal Ilmiah Agribisnis, 2016)
This study was aimed at analyzing: (1) the level of income from peanut agribusiness in Pulubala Sub-district, District of Gorontalo, 2) marketing distribution of peanut agribusiness in Pulubala Sub-district, District of Gorotnalo, 3) the marketing margin of peanut agribusiness in Pulubala Sub-district, District of Gorontalo. This research was conducted in Pulubala Sub-district, District of Gorontalo from August to November 2016 with samples that consisted of 55 farmers and 10 traders. The study used survey method. The data were analyzed using the income analysis, distribution analysis and marketing margin analysis. It revealed the difference on the level of income of the farmers based on land ownership status in peanut agribusiness, which the average owner as well as worker's income was IDR. 2,964,608.08 and the average income per hectare was IDR. 3,631,856.07. Whereas, the tenant farmers' average income was 1DR. 2,930,753.97 with the average income per hectare was IDR. 2,567,083.77. There were three marketing channels for peanut agribusiness in Pulubala Sub-district that comprised of, first marketing channel was from farmer intermediaries big traders consumers. The second channel was from farmer intermediaries small traders consumers. In addition, the third channel was from farmers consumers. The marketing margin in the first channel was IDR.12,500 and in the second channel was IDR. 12,000. The biggest margin was obtained in the first channel, in which the big traders had caused the income of farmers become smaller than the traders were. The third channel had no margin because it was a direct channel. Therefore, the third channel was the most profitable for producer. Keywords: Peanut, Marketing channel, Marketing margin